Worldmark encyclopedia of the states. (Gale virtual reference library, 2016)
Details current geographical, social, and political data, historical narrative, and statistical information on the 50 states, District of Columbia, Puerto Rico, and Caribbean and Pacific dependencies of the United States. Maps, tables, flags and official state seals are included.